Correlation between two‐ and three‐dimensional crystallographic lattices for epitaxial analysis. II. Experimental results. Issue 3 (11th April 2022) - Simbrunner, Josef; Domke, Jari; Sojka, Falko; Jeindl, Andreas; Otto, Felix; Gruenewald, Marco; Hofmann, Oliver T.; Fritz, Torsten; Resel, Roland; Forker, Roman
Abstract : Organic epitaxy is studied experimentally in terms of the correlation of the involved two‐ and three‐dimensional crystallographic lattices. Abstract : While the crystal structure of the polymorph phase can be studied in three dimensions conveniently by X‐ray methods like grazing‐incidence X‐ray diffraction (GIXD), the first monolayer is only accessible by surface‐sensitive methods that allow the determination of a two‐dimensional lattice. Here, GIXD measurements with sample rotation are compared with distortion‐corrected low‐energy electron diffraction (LEED) experiments on conjugated molecules: 3, 4;9, 10‐perylenetetracarboxylic dianhydride (PTCDA), 6, 13‐pentacenequinone (P2O), 1, 2;8, 9‐dibenzopentacene ( trans ‐DBPen) and dicyanovinyl‐quaterthiophene (DCV4T‐Et2) grown by physical vapor deposition on Ag(111) and Cu(111) single crystals. For these molecular crystals, which exhibit different crystallographic lattices and crystal orientations as well as epitaxial properties, the geometric parameters of the three‐dimensional lattice are compared with the corresponding geometry of the first monolayer. A comparison of the monolayer lattice from LEED investigations with the multilayer lattices determined by rotated GIXD experiments reveals a correlation between the first monolayer and the epitaxial growth of three‐dimensional crystals together with lattice distortions and re‐alignment of molecules. The selected examples show three possible scenarios of crystal growth on top of an ordered monolayer: (i) growth of a single polymorph, (ii) growth of three different polymorphs; in both cases the first monolayer serves as template. In the third case (iii) strong lattice distortion and distinct molecular re‐alignments from the monolayer to epitaxially grown crystals are observed. This is the second part of our work concerning the correlation between two‐ and three‐dimensional crystallographic lattices for epitaxial analysis. In the first part, the theoretical basis has been derived which provides a mathematical relationship between the six lattice parameters of the three‐dimensional case and the three parameters obtained for the two‐dimensional surface unit cell, together with their orientation to the single‐crystalline substrate. In this work, a combined experimental approach of GIXD and LEED is introduced which can be used to investigate the effect of the epitaxial monolayer on the structural properties of molecular crystals grown on top.